Contemporary democratic theory - Chambers, Simone (Cambridge ; Hoboken : Polity Press, 2024)
"Is democracy worth saving? Responding to the erosion of democracy, philosophical debates have pivoted from analyzing the best forms of democracy to questioning what is so valuable about democracy to begin with, how we can save it, and whether it is indeed worth saving. Contemporary Democratic Theory charts this pivot and surveys the most important new developments in the philosophical, theoretical, and normative examination of the concept of democracy. Comparisons that dominated 20th century democratic theory - between direct democracy, participatory democracy, deliberative democracy, and agonistic democracy - are in the 21st century giving way to comparisons between democracy and its challengers: epistocracy, technocracy, meritocracy, oligarchy, and autocracy. Philosophical interest in the canonical figures of democratic theory like Aristotle, Rousseau and Mill is being eclipsed by damage control in the face populism, sinking trust in democratic institutions, failing political parties, and the spread of misinformation." --
Chapter 1: Introduction Chapter 2: Justifying Democracy Chapter 3: Equality Chapter 4: Freedom Chapter 5: Instrumentalism 1: Realism Chapter 6: Instrumentalism 2: Performance Skeptics Chapter 7: Instrumentalism 3: Epistemic Democracy Chapter 8: Populism and the People Chapter 9: Representation Chapter 10: Public Sphere Chapter 11: Innovation and Disobedience Chapter 12: Conclusion.
Includes bibliographical references and index.
Keywords: Democracy; Democracy -- Philosophy; demokratia; teoriat; tasa-arvo.; demokrati; teorier; jämställdhet